Facile fabrication of Fe-doped Nb2O5 nanofibers by an electrospinning process and their application in photocatalysis. Issue 1 (23rd December 2020) - Wang, Lu; Li, Ya; Han, Pingfang; Jiang, Yunxia
Abstract : Charge transfer and photocatalysis in Fe-doped Nb2 O5 nanofibers under visible-light irradiation. Abstract : It is of top priority to develop highly efficient visible-light photocatalysts to realize the practical applications of photocatalysis in industry. Niobium pentoxide (Nb2 O5 ) is considered as a potentially attractive candidate for the visible-light-driven photodegradation of organic pollutants. In an effort to enhance its photocatalytic activity, Fe-doped Nb2 O5 nanofibers with various Fe contents (the molar ratios of Fe to Nb were 0.005/1, 0.01/1, 0.03/1 or 0.05/1) were successfully prepared by an electrospinning method. The structural features, morphologies, and optical properties of the as-prepared samples were investigated. Photocatalytic activities of the samples were evaluated through degradation of Rhodamine B (RhB) under visible light irradiation. All the prepared Fe-doped Nb2 O5 nanofibers exhibited much higher activities for degrading RhB solution than the pristine Nb2 O5 nanofibers, and the maximum degradation yield of 98.4% was achieved with the nanofibers (Fe to Nb: 0.03/1) under visible light irradiation for 150 min. The photocatalytic degradation rate fitted a pseudo-first-order equation, and the rate constants of reactions with Fe-doped Nb2 O5 nanofiber (the molar ratios of Fe to Nb were 0.03/1) or pure Nb2 O5 nanofiber were 0.0282 min −1 and 0.0019 min −1, respectively. Doping Fe ions into the nanofibers enhanced the absorption within the visible-light range and reduced the photo-generated electron–hole pair recombination, and thus improved the photocatalytic activity. These attractive properties suggest that the Fe-doped Nb2 O5 nanofibers have great potential for applications in the future to solve pollution issues.